2020
DOI: 10.18203/2320-6012.ijrms20204900
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices in response to COVID-19 pandemic in Indian population

Abstract: Background: The World Health Organization (WHO) had reported COVID-19 disease as a pandemic in March 2020, following which India witnessed more than 29,451 cases on 29th April. Correct knowledge about the disease, the right attitude, and response to infection control recommendations among people is of utmost importance to limit the contagion.Methods: A Cross-Sectional, web-based online study was conducted for five days. The responses (N= 1231) were collected across social networks using snowball sampling. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Study also highlighted that person aged 45+ years, female, urban residents, Indian ethnicity, non-Malaysian, higher education, ever married and good income were more likely to have good practice and all are significant to COVID-19 prevention practices in Malaysia. By systematic review, we also observed age, gender, region and occupation as the significant factor of persons' practice toward COVID-19 (1,23,29,33,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)65). Hence, these findings suggest that health education interventions targeting particular groups such as younger people, men, lower educated persons, people with a less monthly income and rural residents should be designed in order to improve COVID-19 awareness, which can play vital role in improving the practice of individual's preventive attitudes (1,64).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Study also highlighted that person aged 45+ years, female, urban residents, Indian ethnicity, non-Malaysian, higher education, ever married and good income were more likely to have good practice and all are significant to COVID-19 prevention practices in Malaysia. By systematic review, we also observed age, gender, region and occupation as the significant factor of persons' practice toward COVID-19 (1,23,29,33,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)65). Hence, these findings suggest that health education interventions targeting particular groups such as younger people, men, lower educated persons, people with a less monthly income and rural residents should be designed in order to improve COVID-19 awareness, which can play vital role in improving the practice of individual's preventive attitudes (1,64).…”
Section: Discussionmentioning
confidence: 82%
“…Some related survey conducted in Qatar and Iran also revealed high prevalence of having good knowledge toward COVID-19 ( 56 , 57 ). While, a low percentage of Bangladeshis, Indians and Thailand population had good knowledge ( 49 , 54 , 58 ).…”
Section: Discussionmentioning
confidence: 98%
“…Following that, India experienced a disproportionately higher risk of death. Furthermore, subsequent relaxing of restrictions in India and increased movement have resulted in an increase in the disease and reported deaths [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted in the Indian context regarding the assessment of knowledge, attitudes, and practices of various strata of the society, including students, the general public, and they concluded that prevention is possible with measures like vaccination, but none of the studies in best of the knowledge of authors has been published with perception regarding the vaccination safety on vaccinated individuals [11][12][13].…”
Section: Discussionmentioning
confidence: 99%